New faces in the green room: Developing country coalitions and decision-making in the WTO - Mayur Patel (University of Oxford, Global Economic Governance Programme (GEG), 2007)
While the rules-based multilateral trading system represents an important part of the international governance framework, concerns have long been expressed about the legitimacy and accountability of the WTO. In 1999, the dramatic breakdown of the Seattle Ministerial placed the marginalisation of developing countries in key deliberations as one of the central political challenges facing the international trade regime. Historically, trade negotiations in the WTO and prior to that the GATT have proceeded through the creation of "consensus" within restricted inner circle group meetings, traditionally dominated by the Quad - the US, Japan, EU and Canada. The lack of transparency and exclusivity of these meetings, combined with the limited resources of weak states, meant that developing countries found themselves isolated from many decision-making processes. In the face of these disparities and institutional pressures, developing countries have now increasingly sought to build coalitions as the primary means of improving their representation in the WTO.
Keywords: 330